A Preliminary Building Assessment of The Structural Defect on Selected Klinik Kesihatan in Johor - Zaian, Nuramira Syafiqa; Musa, Mohd Kamaruzaman; Mohd Sari, Kamarul Aini (Progress in Engineering Application and Technology, 2022)
A building condition assessment is the process of examining the entire structure and infrastructure, including mechanical and electrical systems equipment, building frames, internal structure and finishes, and building sites. According to the company Perkhidmatan Sokongan Klinik (PSK) there is lot of complaints filled by the building users that there is lot of defects detected on the building of Klinik Kesihatan in Johor. Visual inspection was carried out to evaluate the building’s health and performance in order to determine whether or not it can safely be occupied for another decade. The objectives of this study to identify the types of structural defects on the building and to assess the defect of the structural building on eight selected Klinik Kesihatan in Johor. A qualitative observation was conducted by doing preliminary inspection with visual inspection over the building of Klinik Kesihatan in Johor. The method such as Planned Preventive Maintenance (PPM) checklist, Building Condition Assessment (BCA) also tools of Condition Survey Protocol (CSP) 1 Matrix were used to assess buildings in good condition. A few common minor defects can be found mostly due to cracks at the apron. Analysis has been done and findings overall building rated in fair and good building condition. A conclusion was made by achieved all objectives which is different buildings or structures generate different types of defects and necessitate various levels and types of quality, which are dependent on the building functions, construction or maintenance systems, and materials used. However, further study is required to explore more in repair techniques and selection of materials in the maintenance of selected Klinik Kesihatan in Johor.